2021
DOI: 10.1007/s00592-021-01708-8
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm and gestational diabetes: working conditions, sleeping habits and lifestyle influence insulin dependency during pregnancy

Abstract: Objective Management of gestational diabetes (GDM) is currently changing toward a more personalized approach. There  is a growing number of GDM patients requiring only a single dose of basal insulin at night to achieve glucose control. Well-known risk factors like obesity, parity and family history have been associated with GDM treatment requirements. Sleep quality and lifestyle factors interfering with the circadian rhythm are known to affect glucose metabolism. The aim of this study was to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…(2013) were reported in the supplementary results tables of the other two transcriptome studies ( 22 24 ). Differentially expressed clock genes are consistent with other studies that showed associations between sleep disruptions/night shift work and GDM ( 40 ). Specifically, sleep disruptions in GDM are associated with higher morning blood cortisol and glucose levels, increasing the need for long-acting insulin at night for patients with GDM.…”
Section: Discussionsupporting
confidence: 90%
“…(2013) were reported in the supplementary results tables of the other two transcriptome studies ( 22 24 ). Differentially expressed clock genes are consistent with other studies that showed associations between sleep disruptions/night shift work and GDM ( 40 ). Specifically, sleep disruptions in GDM are associated with higher morning blood cortisol and glucose levels, increasing the need for long-acting insulin at night for patients with GDM.…”
Section: Discussionsupporting
confidence: 90%
“… Calvo–Ferrandiz et al, 2017 [ 38 ] Spain 100 Narcolepsy Questionnaire Higher incidence of GDM in women with narcolepsy with cataplexy. Weschenfelder et al, 2021 [ 40 ] Germany 234 Circadian rhythm disorders 75-g OGTT (IADPSG) Higher need for long-acting insulin therapy in women with circadian rhythm disturbances and GDM. Wilson et al, 2022 [ 39 ] USA 7742 Narcolepsy Derived from registry No association between narcolepsy and GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Light-induced circadian dysregulation has been associated with multiple pregnancy complications including miscarriage 15 17 , preterm birth 17 , 18 , and gestational diabetes 19 . There is compelling evidence that pathophysiological functions regulated by the circadian system contribute to PE, where pregnant women with PE frequently are diagnosed with an abnormal circadian blood pressure rhythm 20 .…”
Section: Introductionmentioning
confidence: 99%